ANALISIS KETIMPANGAN GENDER DALAM PROSES PEMBANGUNAN (Sebuah Tinjauan Sosiologi Historis Terhadap Partisipasi Perempuan Di Bidang Pendidikan) - Zusmelia, Zusmelia (Jurnal Pelangi : Research of Education and Development, 2012)
Despite the recognition of the position and rights of women have undergoneformal judicial progress. However, when viewed from the award obtained, but forgender equality, the practical level is still not encouraging. Women are still assubordinate males, both in the state and the family / household. The main focus ofthis paper discusses about gender inequality in relation to education, and thedevelopment process in Indonesia.The low level of education is a matter of why women still can take their apart in public sectors such as economic, politic, health and so forth. This is due to: 1)the higher the level of education has limited the number of schools available, 2) thehigher the educational level the greater the costs involved, 3) the cultural sector,which assume that girls do not need high school, so it is quite simply to elementaryor junior high school. That's why over the years the government has always triedvarious forms of business / programs that aim to improve the quality of women.Improving the quality of education of women will affect the economic, social,cultural, health and others who in turn will affect fertility. This assumption isreinforced by the increasing role of the mother as the social capital in theneighborhood. This condition will be realized with respect to educational issues first.Low education would be impossible for a woman to go into the public sector or tocarry heavy duty. With the increasing participation of women in education for thefuture, the number of hours worked by an adequate income, women will be achieved.